Pharmacological Inhibition of Fatty Acid-Binding Protein 4 (FABP4) Protects Against Rhabdomyolysis-Induced Acute Kidney Injury - Huang, Rongshuang; Shi, Min; Guo, Fan; Feng, Yuying; Feng, Yanhuan; Liu, Jing; Li, Lingzhi; Liang, Yan; Xiang, Jin; Lei, Song; Ma, Liang; Fu, Ping (Frontiers in Pharmacology, 2018)
Acute kidney injury (AKI) is a common and potentially life-threatening complication. Studies confirmed that circulating FABP4 depended on renal function of AKI patients. In our previous study, FABP4 was found to be involved in the pathogenesis of I/R-induced AKI. However, the function of FABP4 in rhabdomyolysis-induced AKI remains poorly understood. In the present study, we investigated the effect of FABP4 in a murine model of glycerol injection-induced rhabdomyolysis. Following glycerol injection, the mice developed severe AKI as indicated by acute renal dysfunction and histologic changes, companied by the increased FABP4 expression in the cytoplasm of tubular epithelial cells. Pharmacological inhibition of FABP4 by a highly selective inhibitor BMS309403 pretreatment significantly reduced serum creatinine level, proinflammatory cytokine mRNA expression of tumor necrosis factor-α, interleukin-6, monocyte chemoattractant protein 1 as well as attenuated renal tubular damage in glycerol-injured kidneys. Oral administration of FABP4 inhibitor also resulted in a significant attenuation of ER stress indicated by transmission electron microscope analysis and its maker proteins expression of GRP78, CHOP, p-perk, and ATF4 in kidneys of AKI. Furthermore, BMS309403 could attenuate myoglobin-induced ER stress and inflammation in renal proximal tubular epithelial cell line (HK-2). Overall, these data highlighted that renal protection of selective FABP4 inhibitor was substantiated by the reduction of ER stress and inflammation in tubular epithelial cells of rhabdomyolysis-induced injured kidneys and suggested that the inhibition of FABP4 might be a promising therapeutic strategy for AKI treatment.